Development of a procedure to determine internal stresses in concrete bridge members. - Hammerschmidt, Steven F. (Kansas State University, 2011)
With aging and deterioration of bridges, evaluation of existing conditions of their structural elements becomes vital to engineers and public officials when deciding how to repair or replace the structures. The ability to obtain necessary information on these conditions is often expensive and time consuming, especially for concrete bridges where the reinforcement is not available for inspection. Employing the surface-strain relief method could allow for accurate evaluation of aged or damaged prestressed members. The surface-strain relief method was developed to measure initial or pre-existing strains in a concrete member. It involves relieving the strain in the member and measuring the change in strain. Two methods were tested—one used a linear electrical-resistance strain gage and a three-inch-diameter diamond concrete core bit to cut around the gage, and the second method used a laser-speckle imaging device and a diamond cutting wheel to create notches perpendicular to the axis of maximum strain. Both methods measured the change in strain and related it to within 10 percent of the actual fse. The method of cutting notches and the laser-speckle imaging device provided a simpler method to be implemented in the field, while the coring method achieved a higher level of accuracy and precision.
Keywords: Prestress; Concrete; Bridge; Residual stresses; Civil Engineering (0543)